2018
DOI: 10.1002/jgf2.196
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone ileus with spontaneous evacuation: A case report

Abstract: A 65‐year‐old man was referred to our hospital for abdominal pain. He had a history of enterotomy with stone extraction for gallstone ileus. On abdominal computed tomography, a stone measuring 32 × 28 mm lodged in the jejunum was identified. He was diagnosed with gallstone ileus and treated using a nasal ileus tube. Four days after admission, computed tomography showed that the stone had passed into the rectum. The gallstone was spontaneously evacuated on the same day. A fistula with the gallbladder was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Migrating through the fistula, large gallstones could cause intestinal obstruction, but they could also migrate to any part of the gastrointestinal tract without causing any symptoms. The most commonly obstructed part is the terminal ileum, which leads to the gallstone ileus [2,4,10]. Classic abdominal radiographic signs of pneumobilia, mechanical bowel obstruction, and ectopic gallstone were first described by Rigler, but in around one half of the patients there are usually two out of three signs [1,3,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Migrating through the fistula, large gallstones could cause intestinal obstruction, but they could also migrate to any part of the gastrointestinal tract without causing any symptoms. The most commonly obstructed part is the terminal ileum, which leads to the gallstone ileus [2,4,10]. Classic abdominal radiographic signs of pneumobilia, mechanical bowel obstruction, and ectopic gallstone were first described by Rigler, but in around one half of the patients there are usually two out of three signs [1,3,11].…”
Section: Discussionmentioning
confidence: 99%
“…Душан Шапоњски 1 , Александра Ђурић-Стефановић 1,2 , Александра Јанковић 1 , Милица Митровић-Јовановић 1 , Стефан Кмезић 3 , Слађана Михајловић 2,4 , Иван Поповић 5 , Ђорђије Шарановић 6,7 1 Клинички центар Србије, Прва хируршка клиника, Центар за радиологију и магнетну резонанцу, Одељење дигестивне радиологије, Београд, Србија; 2 Универзитет у Београду, Медицински факултет, Београд, Србија; 3 Клинички центар Србије, Прва хируршка клиника, Београд, Србија; 4 Клиничко-болнички центар "Др Драгиша Мишовић -Дедиње", Београд, Србија; 5 Општа болница "Стефан Високи", Смедеревска Паланка, Србија; 6 Општа болница "Медигруп", Београд, Србија; 7 Универзитет у Бањој Луци, Медицински факултет, Бања Лука, Република Српска, Босна и Херцеговина…”
Section: сажетакunclassified
See 1 more Smart Citation
“…These authors found that this sign was present in 24% of patients at the time of hospitalization. In Bouveret's syndrome, a dilated stomach is expected to be seen on a simple abdominal radiograph due to gastric obstruction [37,42,43,[46][47][48][49]. Cappell et al [31], in a review of 64 cases of Bouveret syndrome, found pneumobilia (39%), calcified upper right quadrant mass or gallstones (38%), and gastric distension (23%) as relatively common findings and dilated loops of the intestine (14%).…”
Section: Normal Abdominal Radiographymentioning
confidence: 99%
“…Gallstone ileus is more common in the elderly and up to 80% -90% of affected patients have medical comorbidities [2]. The ratio of occurrence in females to males is 3.5:1 [3].…”
Section: Introductionmentioning
confidence: 99%